Current situation with forest radioactive contamination in Volyn and Zhytomyr Polissia - Жуковський , О. В.; Краснов , В. П.; Курбет , Т. В.; Шелест , З. М. (Forestry and Forest Melioration, 2023)
Introduction The accident at the Chornobyl NPP led to a radioactive contamination of huge forest areas of Ukrainian Polissia and the prohibition of forestry and logging operations as well as the revision of numerous forest use regulations. A large-scale survey on forest radioactive contamination in Ukraine was carried out in 1991–1992. Since that time, the radiological situation in forests has gradually changed. When studying 137Cs redistribution in forest soils, the researchers found that since the radionuclide had penetrated into the forest ecosystems, it had significantly deepened into the soil; thus, it is necessary to revise the methodology regarding the depth of sampling. The aim of the study was to analyze and summarize modern materials on forests’ radioactive contamination, as well as to formulate proposals for the unification of forest surveying methodology for their further rehabilitation. Materials and Methods The analysis was conducted using the Zhytomyr Regional Department of Forestry and Hunting database on the survey of forest stands (1991–1992), as well as the modern relational database “Forest Fund of Ukraine”. The distribution of 137Cs in forest soils was investigated on permanent sample plots, which were established in 1991 in moist fairly infertile pine site types and fairly fertile site types. The radioecological indicators of soils were studied according to the methods generally accepted in radioecology and soil science. Results The study showed that 56,816.9 hectares of forest stands in the investigated region have to be surveyed for their rehabilitation, while according to the 1991–1992 survey data, the areas were not so vast in the region – 48,800 hectares. The obtained up-to-date results of repeated surveys demonstrate a decrease in the levels of forest radioactive contamination in all surveyed forest compartments. This decrease ranges from 1.2 to 15.6 times. Also, these materials testify to the significant mosaic nature of 137Cs soil contamination density within forest compartments (the coefficient of variation reaches 52.5 %). The density values of radioactive soil contamination demonstrate a marked mosaic nature more specifically. For example, in a separate compartment (No. 85, Luhyny Forestry – Luhyny Forestry branch of the State Enterprise "Forests of Ukraine") the value ranged from 62.9 to 466.2 kBq·m-2. A similar radiation situation is observed in other forest compartments. The results show a significant 137Cs penetration into soils of moist fairly infertile pine site types and fairly fertile site types. However, there are certain differences in this process. In moist fairly infertile pine site types, a significant amount of radionuclide is contained in forest litter – 13.68 %, while in moist fairly fertile site types only 3.11 %. However, there is 74.7 % of the radionuclide in a 10-cm layer of the mineral part of soil in moist fairly infertile pine site types, and 87.26 % in moist fairly fertile site types. Conclusions The findings revealed that currently there is a significant mosaic of radioactive contamination of forest compartments. Since the accident at the Chornobyl nuclear power plant happened, there has been a significant decrease in the density of 137Cs soil contamination, which is usually associated with its natural decay. At the same time, it was found that these decreases are more significant and cannot be explained only by objective reasons. It was found that the mineral part of soil accounts for 86.32–96.89 % of 137Cs total activity. And forest litter accounts for 3.11–13.68 % of the radionuclide total activity depending on the forest vegetation conditions. The materials of up-to-date radionuclide distribution in soil indicate that it is necessary to make changes in the method of soil selection and carry it out to a depth of at least 20–30 cm. 1 Fig., 5 Tables, 11 Refs.